Osage Orange, Honey Locust and Black Locust Seed Meal Adhesives Employed to Fabricate Composite Wood Panels - Brent Tisserat; Rogers Harry-O’kuru (Fibers, 2019)
Seed meal of three trees common to the Midwest region of the USA (Honey locust, Gleditsia triacanthos L., family Fabaceae), Osage orange (Maclura pomifera (Raf.) Schneid., family Moraceae) and Black locust (Robinia pseudoacacia L., family Fabaceae) were tested for their adhesive abilities. Seed meals were employed at dosage levels of 10, 15, 25, 50, 75, and 100% reinforced with Paulownia elongata L. wood (PW) or Osage orange wood (OOW) chips to fabricate composite wood panels (CWPs). A comparison of the flexural properties of various tree seed meal CWPs reinforced with PW showed that their flexural properties met or exceeded European Union standards. However, their dimensional stability properties were inferior to nominal standards. Therefore, tree seed meal CWPs could probably have applications in interior environments where such CWPs accept negligible dimensional stability standards.